Willingness to Pay to Conserve Tenualosa toli(Terubok) - Bakeri, N. A.; Dayang Affizzah, Awang Marikan; Abdullah, A. M.; Ashraf-Roszopor, R. (Human Resource Management Academic Research Society, 2020)
Over the year, the population of local terubok(Tenualosa toli)is being threatened due to over-exploitation. Terubok is one of the famous and important commercially fish in Malaysia which only found in Sarawak rivers. Nowadays, the landing of local terubok are very limited and difficult to obtain since 1980s. Environmental goods like terubok has a value to society, however, it is difficult to obtain and express these economic values in monetary terms. One of the methods that commonly used to evaluate non-market valuation which is Contingent valuation method (CVM) was used in this study to estimate the willingness-to-pay (WTP) of local communities to conserve terubok. A dichotomous choice contingent valuation method (DC-CVM) in single bound formulation was employed in this study. The general objective of this study is to examine the monetary value that local people are willing to pay to conserve terubok in Sarawak. The result shows that WTP of Yes decreases as the price of the offer increases. Result indicates that respondents are willing to pay at an average of RM31 per annum for sustainability ofTerubok.